The Effectiveness of Moral Development in Early Childhood According to Hadith - Yulia Sukma Rahma Pratiwi; Tamami Tamami (Gunung Djati Conference Series, 2021)
This study aims to discuss the effectiveness of moral development in early childhood according to the hadith. This research is a qualitative type that applies literature study with content analysis. The results and discussion of this study include an overview of early childhood, hadith on moral development, and methods that can be used in learning and moral development in early childhood. This study concludes that moral inculcation at an early age is very important, especially with today's conditions where there is a crisis of exemplary. Moral education must be carried out from an early age, before his character and personality are affected by an environment that is not in accordance with religious guidance. Therefore, in the coaching process requires a method that must really be considered in its application, so that it can affect every child's development. This study recommends for further research on the effectiveness of moral development in early childhood according to hadith through field studies with a case study approach